Pembinaan Akhlak Siswa Melalui Integrasi Pesantren Dan Sekolah (Studi Analisis Di Smk Ma’arif 1 Kebumen) - Mugiarto (Jurnal Kridatama Sains dan Teknologi, 2021)
Abstract The role of the cottage pesantern in fostering morals already uncontested again with a lot of challenges and temptations for the life of the students. This study aims to describe and learn about the role of boarding school in fostering promiscuity teen in SMK Ma'arif 1 Kebumen. This study is a field research and types of qualitative research. Data collection techniques using observation, documentation and interviews. The data analysis technique that used qualitative descriptive analysis which consists of 3 grooves of the activities that take place simultaneously, namely data reduction, data presentation and withdrawal of conclusion. This technique is used as a reference for the writing of the results of research and facilitate understanding of the description, which presented the results of the end of the study. The research will be looking the role of the pesantren in the development of character in SMK ma'arif 1 Kebumen. Expected from the coaching to the youth as the next generation can give birth to a generation better. The generation that is able to maintain values but can contribute to the development of the Indonesian nation from the physical and spiritual. Keywords: Coaching, Chastity, Integration, Boarding School, School.